1991
DOI: 10.1136/oem.48.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Neurological long term consequences of deep diving.

Abstract: Forty commercial saturation divers, mean age 34-9 (range 24-49) years, were examined one to seven years after their last deep dive (190-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Permanent health problems have been observed in 20-30% of cases with neurological DCS [8]. In studies of professional divers, the effects of cumulative diving exposure and decompression sickness have been observed on lung function and on the central nervous system [9][10][11][12][13][14][15]. In addition, diving is associated with dysbaric osteonecrosis and hearing impairment [16][17][18] and exposure to life threatening events may cause serious psychological distress [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Permanent health problems have been observed in 20-30% of cases with neurological DCS [8]. In studies of professional divers, the effects of cumulative diving exposure and decompression sickness have been observed on lung function and on the central nervous system [9][10][11][12][13][14][15]. In addition, diving is associated with dysbaric osteonecrosis and hearing impairment [16][17][18] and exposure to life threatening events may cause serious psychological distress [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In the group with serious incident, we found that in three patients, the first symptoms appeared under water (5, 9, 11); and in three others (6,10,12) return to the surface was as an emergency with the immediate appearance of symptoms. Of these six individuals, four had major sequelae.…”
Section: Discussionmentioning
confidence: 84%
“…[42,58]. In another study Todnem et al [59] examined 40 saturation divers 1-7 years after their last deep dive and 100 controls. These divers also reported significantly more concentration difficulties, had more abnormal neurological findings and more often abnormal EEG.…”
Section: Epidemiological Studiesmentioning
confidence: 95%